LEGAL AND CONTRACTUAL RISKS IN MERGERS AND ACQUISITIONS - R. A. Fayzullin (Финансы: теория и практика)
The paper analyzes the civil institutions of legal and contractual risks in mergers and acquisitions and gives an insight into the legal nature of their mechanisms in terms of the theory and practice of the civil law. Some of the legal problems and gaps in the law are identified and solutions are proposed. The importance of the topic is dictated by the cross-border nature of mergers and acquisitions. The legal analysis was made unadjusted for the changes made in the Civil Code. Examples of risks are provided and risks arising from the implementation of various procedures related to the purchase or sale of shares, including due diligence procedures, are analyzed. The basic concepts of the legal and contractual risks used in statutory instruments are examined and contradictions and flaws of the definitions are highlighted. Attention is paid to the analysis of concepts and interpretations proposed by Soviet Civil Law experts as well as to the interrelations between legal, economic and business risks. Classifications of legal and contractual risks are discussed.